FAKTOR-FAKTOR PENENTU MANAJEMEN MUTU TERPADU PADA PERGURUAN TINGGI DI KOTA AMBON - Zainuddin Latuconsina (Soso-Q : Jurnal Manajemen, 2018)
The phenomenon of education that can be destructive even become a killer pest college education system in Ambon City is that students still consider that the diploma is only a means to be pursued without understanding the meaning of education which then the diploma will be used as capital to become civil servants, or who will eventually dive to politics and run for legislative (DPRD). Another fact that is also quite apprehensive is still a lot of students at universities in Ambon City who copy and paste the work of others to be a thesis to complete the study (plagiarism). So without us knowing it has now become a tradition in college.The main objective of this research is to identify the determinants of total quality management at universities in Ambon City. This research uses Confirmatory Factor Analysis (CFA) to identify the determinants of total quality management at universities in Ambon City.The results showed that the determinants of total quality management in higher education are learning process, study program curriculum, human resources, student affairs, infrastructure and facilities, academic atmosphere, finance, research and publication, community service and governanceKeywords: Total quality management, higher education, education